تحليل انحرافات تكلفة التحويل في ظل البيئة التصنيعية الحديثة - دراسة حالة - جديد, غيث محمد (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تركزت الانتقادات المرتبطة بالمدخل التقليدي لتحليل انحرافات تكلفة التحويل في استخدام انحرافات الحجم لقياس استغلال الطاقة الإنتاجية, وإهمال الزيادة في الإنتاج, وكذلك استخدام ساعات العمل, ووقت تشغيل الآلات كأساس لحساب معدلات تحميل تكاليف التحويل, وحساب الانحرافات. ولما كان تحليل الانحرافات ليس مقتصراً على مجموعة محددة من المتغيرات, وأن المتغيرات المستخدمة في التحليل يمكن أن تتغير حسب ما يستجد ويظهر من ظروف واحتياجات, لذلك فإنَّ تحليل الانحرافات بصورته الراهنة لا يوفِّر معلومات مناسبة عن الموقف التنافسي للوحدة الاقتصادية من الناحية التكاليفية. من هنا تبرز ضرورة تحسين وتعديل التحليل التقليدي لانحرافات تكلفة التحويل في ظل احتياجات واستراتيجيات نظم التصنيع الحديثة, وذلك من أجل تطوير تحليل الانحرافات بصورة تعالج أوجه القصور التي وجهت لهذا الأسلوب, وبما يحسن من دور نظام التكاليف المعيارية في دعم نظم الرقابة وتقويم الأداء, وتحقيق إستراتيجية التحسين المستمر. يتناول هذا البحث دراسة الانتقادات التي وجهَّت إلى الأسلوب التقليدي لتحليل انحرافات تكلفة التحويل, ومن ثم تطبيق الأسلوب الحديث لتحليل انحرافات تكلفة التحويل وبما يتلاءم مع متطلبات بيئة التصنيع الحديثة, وذلك في شركة مصفاة بانياس, وقد توصل الباحث إلى مجموعة من النتائج أهمها: لقد أثرت التغيرات التي حدثت في ظل البيئة التصنيعية الحديثة على التحليل التقليدي لانحرافات تكلفة التحويل. لا يشجع التحليل التقليدي لانحرافات تكلفة التحويل على التحسين المستمر. · لا يفصح التحليل التقليدي لانحرافات تكلفة التحويل عن تحركات المخزون بأنواعه المختلفة. إن الانحراف الكلي لتكلفة التحويل في شركة مصفاة بانياس سلبي بمقدار (399845730), أي أن تكلفة التحويل الفعلية أكبر من تكلفة التحويل المعيارية للإنتاج الفعلي. The criticisms connected with the traditional approach for variance analysis of conversion cost focused on using variance of volume for measuring exploitation of productive capacity, and negligence of increasing in the production, also using working hours, and the time of machines working as a basis for counting carrying rates of conversion costs, and counting the variance. When variance analysis was not restricted in determined group of changes, and the changes which are used in the analysis can change according to what develops and appears of situations and needs, so variance analysis in its present form does not provide suitable information about the competitive attitude of economic unit from costing side. Therefore, it is necessary to improve and modify the traditional method of variance analysis of conversion cost under needs and strategies of modern industrial systems, to fit the variance analysis in a way that treats the criticisms which were directed to this style, the role of standard costs system in support of control systems and performance correction, and achievement the strategy of continuous improvement. The research tries to study the criticisms which were directed to the traditional method of variance analysis of conversion cost, then to apply the modern method of variance analysis of conversion cost, and which suits with requirements of modern industrial environment, in company of Banias Refinery, and the researcher reaches to series of results, the most important of those are: The changes which happened in modern industrial environment affected the traditional analysis of variance of conversion cost; The traditional analysis of variance of conversion cost doesn't encourage the continuous improvement; The traditional analysis of variance of conversion cost doesn't refer to movements of stock in its different types; and The total variance of conversion cost in company of Banias Refinery is (-399845730) , that is actual conversion cost bigger than standard conversion cost to the actual production.